2017
DOI: 10.18203/2320-6012.ijrms20174547
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based medical use of aloe vera extracts, short review of literature

Abstract: The use of aloe vera is being promoted for a large variety of conditions. The aim of this review was to summarize all available research papers on aloe vera preparations with a view to providing evidence for or against its clinical effectiveness. Independent literature searches were conducted in PubMed. All studies of controlled clinical trials, observational studies and case series were included. There were no restrictions on the language of publication. All studies were read by all authors and data were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Acute Oral Toxicity Study: A detailed study on the acute oral toxicity of these plants was already reported by us revealed that the BS and AB extracts were non-toxic up to the dose of 2000 mg/kg 11,12 .…”
Section: In-vivo Anti-arthritic Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…Acute Oral Toxicity Study: A detailed study on the acute oral toxicity of these plants was already reported by us revealed that the BS and AB extracts were non-toxic up to the dose of 2000 mg/kg 11,12 .…”
Section: In-vivo Anti-arthritic Activitymentioning
confidence: 95%
“…The preliminary acute toxicity of microsponge and individual plant extract showed no significant toxic effects upto 2000 mg/kg in rodents 11 . In light of the results of the literature studies on individual extracts, it was found to have good anti-inflammatory and anti-arthritic activities 12,13 . With this background, the present study was planned to screen anti-arthritic effect of a microsponge constituting powder extract of resins of B. serrata and leaves of A. barbadensis against Freund's complete adjuvant (FCA) induced arthritis in Male Wistar rats.…”
mentioning
confidence: 99%
“…Inside the skin there are bundles of vessels that are responsible for the transportation of substances such as water (xylem) and starch (phloem). All of them contain 75 potentially active constituents: vitamins, enzymes, minerals, sugar, lignin, saponins, salicylic acid, and amino acids which are very effective as an anti-inflammatory, antiseptic, anti-viral, antioxidant, and wound treatment 45. Effect of Aloe Vera on the Transforming Growth Factor (TGF-β) Expression in White Rat Cornea Wistar Strain Model for Chemical Base Trauma.…”
mentioning
confidence: 99%